Financial Annexation, Green Innovation and Carbon Neutrality in China - Sun, Yunpeng; Li, Ying; Wang, Yujing; Bao, Qun (Frontiers in Environmental Science, 2022)
This article used data from 1980 to 2019 to examine the relationship between financial annexation, financial development, green innovation, and CO2 emissions in China. This review provides vital information to policymakers on how to go to preventative and therapeutic measures to reduce CO2 discharges in many sectors and demonstrates that innovation in the energy sector may help alleviate environmental change through energy productivity. The review used an autoregressive disseminated slack (ARDL) model to determine the dynamic coefficients for both the study’s long- and short-term periods. This study used the autoregressive circulated slack (ARDL) approach since it performs better than any alternative strategies in small cases, as was the case in this research. The ARDL and DARDL models show that CO2 emissions in China are increasing as a result of increased energy consumption and economic growth. Based on the findings, it is advised that China’s approach creators take on such sustainable power sources and improve them so that they may help meet the growing need for energy by replacing outdated traditional energy sources like coal, gas, and oil with them.